2019
DOI: 10.3390/su11226235
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Environmental Impacts of Meatless and Meat-Containing Meals in the United States

Abstract: This study compares the environmental impacts of meatless and meat-containing meals in the United States according to consumption data in order to identify commercial opportunities to lower environmental impacts of meals. Average consumption of meal types (breakfast, lunch, dinner) were assessed using life cycle assessment. Retail and consumer wastes, and weight losses and gains through cooking, were used to adjust the consumption quantities to production quantities. On average, meatless meals had more than a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 56 publications
1
11
0
1
Order By: Relevance
“…The pizza type-specific estimates presented in this analysis are indicative of "extra meat" and "extra vegetable" pizzas impacts, with the latter generating a substantially lower carbon footprint. While this finding is in agreement with previous estimates for pizzas [37] and other mixed dishes [9,10,14,38,39], it should be noted that ingredient composition might vary greatly within pizza types that may considerably influence the impact of individual foods. This analysis also showed that the choice of the decomposition method has a noteworthy influence on the carbon footprint of individual foods and daily food intake.…”
Section: Discussionsupporting
confidence: 93%
“…The pizza type-specific estimates presented in this analysis are indicative of "extra meat" and "extra vegetable" pizzas impacts, with the latter generating a substantially lower carbon footprint. While this finding is in agreement with previous estimates for pizzas [37] and other mixed dishes [9,10,14,38,39], it should be noted that ingredient composition might vary greatly within pizza types that may considerably influence the impact of individual foods. This analysis also showed that the choice of the decomposition method has a noteworthy influence on the carbon footprint of individual foods and daily food intake.…”
Section: Discussionsupporting
confidence: 93%
“…We also considered the three endpoint indicators: damage to human health, damage to ecosystems, and damage to resource availability. The main strength of this methodology is that it ensures that the different impacts are not assessed more than once in different indicators, and thus ReCiPe scores are extensively used in the life cycle impact assessments [13,[58][59][60][61].…”
Section: Life Cycle Impact Assessmentmentioning
confidence: 99%
“…A number of LCA studies have been published about meals, for example, university canteen meals (Cooreman-Algoed et al, 2020), low-carbon meals in public schools (Batlle-Bayer et al, 2021) and compiling existing LCA results into datasets that permit meal-based calculations for catering to dependent senior citizens (Saxe et al, 2019). It is also possible to use the meal as the function with an appropriate functional unit (Ernstoff et al, 2019a;García-Herrero, De Menna and Vittuari, 2019).…”
Section: Q5: Will the Lca Consider Complex (Or Simple) Food Items Whe...mentioning
confidence: 99%